Biophysical and molecular characteristics of senescing leaves of two Norway maple varieties differing in anthocyanin content - Rantala Marjaana; Mulo Paula; Tyystjärvi Esa; Mattila Heta (WILEY, 2025)
Disassembly and degradation of the photosynthetic protein complexes during autumn senescence, a vital step to ensure efficient nutrient relocalization for winter storage, is poorly understood. Concomitantly with the degradation, anthocyanins are often synthesized. However, as to why leaves accumulate red pigments, no consensus exists. One possibility is that anthocyanins protect senescing leaves from excess light. In this study, we investigated the pigment composition, photosynthetic performance, radical production, and degradation of the photosynthetic protein complexes in Norway maple (Acer platanoides) and in its highly pigmented, purple-colored variety (Faassen's black) during autumn senescence, to dissect the possible roles of anthocyanins in photoprotection. Our findings show that senescing Faassen's black was indeed more resistant to Photosystem II (PSII) photoinhibition, presumably due to its high anthocyanin content, than the green maple. However, senescing Faassen's black exhibited low photosynthetic performance, probably due to a poor capacity to repair PSII. Furthermore, an analysis of photosynthetic protein complexes demonstrated that in both maple varieties, the supercomplexes consisting of PSII and its antenna were disassembled first, followed by the degradation of the PSII core, Photosystem I, Cytochrome b6f, and ATP synthase. Strikingly, the degradation process appeared to proceed faster in Faassen's black, possibly explaining its poor PSII repair capacity. The results suggest that tolerance against PSII photoinhibition may not necessarily translate to a better fitness. Finally, thylakoids isolated from senescing and non-senescing leaves of both maple varieties accumulated very little carbon-centered radicals, suggesting that thylakoids may not be a major source of reactive oxygen species in senescing leaves.